Understanding Impact Feedback on English Writing Ability Among High School Students - Laila Isroyani; Siti Raodatul Warni Mukti; Muslimaini Muti’ain; Selamet Riadi Jaelani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This study aims to understand feedback on English writing skills among high school students. Effective feedback is recognized as an important factor in developing students' English writing skills. This study adopts a qualitative approach to explore students' perceptions and experiences of receiving feedback from teachers or peers and how this affects their writing ability. The research method involved in-depth interviews with several high school students representing various levels of writing ability. The data collected was analyzed thematically to identify general patterns and differences in their perceptions of feedback and their writing abilities. In addition, questionnaires were also used to collect additional data about students' preferences and views on certain feedback. The results of the study show that constructive, specific, and directed feedback positively affect students' English writing abilities. Participants stated that supportive feedback and practical guidance were very helpful in improving the quality of their writing. In addition, this study revealed differences in feedback preferences between students with different levels of writing ability.